A Survey on Quality Changes in Positive, Negative and Combined Switching Strategies in Control of Three Phase Matrix Converter - Mohammad Sarvi; Iman Soltani; Hossein Faramarzi (International Journal of Applied Power Engineering (IJAPE), 2014)
In this paper uses positive, negative and combined switching strategies for three phase ac/ac matrix converter .the author compares these strategies. The performance comparison of these three strategies is made under balanced operation. The simulation of three phase matrix converter feeding a three phase load was accomplished by means of the matlab/simulink software. After the simulation the comparison of the waveforms THD in three switching sequence is done. It must be mentioned that the duty cycle of the whole switches in the converter is according to Venturini switching algorithm